THE EFFECTIVENESS OF MATHEMATICS LEARNING USING THE SYNTHETIC ANALYTIC APPROACH OF MATHEMATICS LEARNING OUTCOME AT ELEVEN GRADE STUDENT - Fathinnisa Nus Islami; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Lacking students actively in the learning process will affect the student learning outcomes, especially in mathematics. Using the Synthetic Analytic Approach is expected to increase students' attractiveness towards mathematics learning to accomplish mathematics problems. Results of mathematics learning students' class XI Social Sciences (IPS) MAN 1 Garut are still low because no students who meet the Minimum Completeness Criteria (MCC) have been determined school. This study aims to determine the effectiveness of learning using Synthetic Analytic Approach of mathematics learning outcomes at Eleven Grade Student of State Islamic Senior high School (MAN) 1 Garut even semester in the Academic year 2016/2017 on the subject of Peluang. This study's population were all students of class eleven grade Student of MAN 1 Garut even semester in 2016/2017. The sample's selection was made using Random Sampling of the class, the class taking the sample by lottery. The sample is a class XI IPS 5 as class Experiment and class XI IPS 4 as class Control. The data collection method used is the method of documentation and testing. The instrument used in mathematics learning outcomes test. The Analyzing of the data in this hypothesis is a t-test.  This research on the significance level of 5% and dk = 66 indicates that: (1) There are differences in the mathematics learning outcomes that use the Synthetic Analytic Approach and the use of Expository Approach. It can be seen that  is bigger than  = . (2) mathematics learning using the Synthetic Analytic Approach is more effective than the use of the Expository Approach. It can be seen that  is bigger than  = .